Identifikasi Karakter Kerja di Industri Otomotif Untuk Lulusan SMK Jurusan Teknik Sepeda Motor di Blitar - Mawahib, Agus; Nurhadi, Didik; Herwanto, Heru Wahyu (Universitas Nahdlatul Ulama Blitar, 2025)
This study aims to identify the work characteristics of vocational school graduates majoring in Motorcycle Engineering in the automotive industry through a qualitative descriptive approach. Data collection was conducted through observation, in-depth interviews, and documentation at three official Honda workshops in Blitar: AHASS MPM, AHASS PSM, and AHASS Kademangan. Data analysis was performed using triangulation of sources and methods to ensure the research results are valid, systematic, and in-depth. The research results indicate that the work standards for mechanics include a minimum SMK TSM diploma, mastery of technical competencies, compliance with SOPs, and the application of good work characteristics such as discipline, religiosity, thoroughness, diligence, concern, honesty, responsibility, communication skills, creativity, innovation, teamwork, and perseverance. However, the application of work character traits among SMK graduates in the automotive industry is not yet fully consistent, particularly in terms of religiousness, meticulousness, perseverance, communication skills, teamwork, resilience, creativity, and innovation. Schools and industries need to establish more intensive collaboration through internship programs, training, and continuous evaluation to ensure graduates possess both technical competencies and work character traits aligned with industry standards.